IMPLIKASI LANDASAN PENDIDIKAN TERHADAP KURIKULUM - Fahruddin; Habib Anwar Al- Anshari (STKIP Subang, 2026)
This study presents a comprehensive analysis of the urgency of the foundation of education in formulating an adaptive and relevant curriculum in Indonesia. The main problem identified is the frequent failure of education policy implementation due to the weak underlying philosophical, sociological, psychological, and technological foundations. The phenomenon of